2021
DOI: 10.1056/nejmoa2029849
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Neutralizing Antibody LY-CoV555 in Outpatients with Covid-19

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (Covid-19), which is most frequently mild yet can be severe and life-threatening. Virus-neutralizing monoclonal antibodies are predicted to reduce viral load, ameliorate symptoms, and prevent hospitalization. Methods In this ongoing phase 2 trial involving outpatients with recently diagnosed mild or moderate Covid-19, we randomly assigned 452 patients to receive a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
1,360
7
27

Year Published

2021
2021
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,272 publications
(1,451 citation statements)
references
References 22 publications
57
1,360
7
27
Order By: Relevance
“…22 Preliminary results of the BLAZE-1 study, provided only for the comparison between LY-CoV555 monotherapy and placebo, showed a significant decrease in the viral load at d 11 (the primary outcome) in patients receiving the 2800-mg dose as compared the placebo group a reduction in the rate of hospitalizations (including emergency department admissions) on d 29 (1.6% in the LY-CoV555 group and 6.3% in the placebo group), a progressive reduction in symptom severity from d 2 to 11) and a good tolerability profile. 20,23 Among the three doses tested (700 mg, 2800 mg, or 7000 mg) the one for which a statistical significant difference was observed is the intermediate (at d 11, difference −0.53 95% confidence interval, CI, −0.98 to −0.08), probably due to the size of the sample (about 100 per investigated group). 20,24 However, the authors noted that this difference observed in the reduction of viral load at d 11 might not be clinically meaningful because it could be associated with the natural course of COVID-19.…”
Section: Ly-cov555 and Ly-cov016mentioning
confidence: 93%
See 1 more Smart Citation
“…22 Preliminary results of the BLAZE-1 study, provided only for the comparison between LY-CoV555 monotherapy and placebo, showed a significant decrease in the viral load at d 11 (the primary outcome) in patients receiving the 2800-mg dose as compared the placebo group a reduction in the rate of hospitalizations (including emergency department admissions) on d 29 (1.6% in the LY-CoV555 group and 6.3% in the placebo group), a progressive reduction in symptom severity from d 2 to 11) and a good tolerability profile. 20,23 Among the three doses tested (700 mg, 2800 mg, or 7000 mg) the one for which a statistical significant difference was observed is the intermediate (at d 11, difference −0.53 95% confidence interval, CI, −0.98 to −0.08), probably due to the size of the sample (about 100 per investigated group). 20,24 However, the authors noted that this difference observed in the reduction of viral load at d 11 might not be clinically meaningful because it could be associated with the natural course of COVID-19.…”
Section: Ly-cov555 and Ly-cov016mentioning
confidence: 93%
“…In this regard, the reduction of hospitalization or emergency department admission rates at d 29 represents a more relevant finding. 23,24 Mostly based on this latter result, the request for Emergency Use Authorization (EUA) for the combination therapy in patients with mild-tomoderate COVID-19 was announced by Eli Lilly in October 2020, and the agreement with the US government for supplying vials in the first 2 months after authorization has been carried out. 25 The ongoing Phase 3 trial BLAZE-2 (NCT04497987), scheduled to enroll 2400 patients, evaluates the prevention of SARS-CoV-2 infection by administration of LY-CoV555 in skilled nursing, assisted living facility staff, and residents.…”
Section: Ly-cov555 and Ly-cov016mentioning
confidence: 99%
“…Although data associated with patient's symptom were consistent which showed a reduction in the severity of symptom on day 2 in LY-CoV555 group. Additionally, safety profile was relatively equal in both LY-CoV555 and placebo group which indicates that the treatment is safe [23].…”
Section: Ly-cov555(bamlanivimab)mentioning
confidence: 87%
“…The results from the interim analysis of a phase 2 trial of LY-CoV555 indicated that only one dose (2,800 mg) of LY-CoV555 showed accelerated natural decline in viral loads over time, whereas the other two doses (7,000 mg and 700 mg) did not significantly reduce viral loads by day 11 (ref. 16 ). On 26…”
Section: Preclinical Development and Clinical Trialsmentioning
confidence: 99%